Genome size drives morphological evolution in organ‐specific ways. (1st July 2022) - Itgen, Michael W.; Natalie, Giovanna R.; Siegel, Dustin S.; Sessions, Stanley K.; Mueller, Rachel Lockridge
Abstract: Morphogenesis is an emergent property of biochemical and cellular interactions during development. Genome size and the correlated trait of cell size can influence these interactions through effects on developmental rate and tissue geometry, ultimately driving the evolution of morphology. We tested whether variation in genome and body size is related to morphological variation in the heart and liver using nine species of the salamander genus Plethodon (genome sizes 29–67 gigabases). Our results show that overall organ size is a function of body size, whereas tissue structure changes dramatically with evolutionary increases in genome size. In the heart, increased genome size is correlated with a reduction of myocardia in the ventricle, yielding proportionally less force‐producing mass and greater intertrabecular space. In the liver, increased genome size is correlated with fewer and larger vascular structures, positioning hepatocytes farther from the circulatory vessels that transport key metabolites. Although these structural changes should have obvious impacts on organ function, their effects on organismal performance and fitness may be negligible because low metabolic rates in salamanders relax selective pressure on function of key metabolic organs. Overall, this study suggests large genome and cell size influence the developmental systems involved in heart and liver morphogenesis.